Correlation between Plasma Soluble CD36 Levels with Body Mass Index of Breast Cancer Patients in the Indonesian Population - Rachman, Andhika; Irawan, Cosphiadi; R.R., Aditia; Koesnoe, Sukamto; Wijaya, Indra (Indonesian Society for Cancer Chemoprevention, 2023)
The cluster of differentiation 36 (CD36) is a multiligand receptor protein that plays a role in lipid metabolism. Its biological functions involve lipid uptake, immune recognition, inflammation, molecular adhesion, and tumor metastasis. Soluble CD36 (sCD36) is the circulating form of CD36 in plasma. Research on the role of sCD36 in breast cancer is limited. This study aimed to investigate sCD36 concentration and evaluate the correlation between sCD36 concentration and BMI in breast cancer patients. This is a multi-center cross-sectional study done from June 2018 to February 2019 in Indonesia. Consecutive sampling was done for women with invasive breast cancer aged 18-70. Patients with locoregional recurrences, multiple comorbidities, diabetes, stroke, or liver impairment were excluded. Patients were grouped based on their BMI into normo-weight and overweight/obese. Plasma sCD36 was analyzed using Bioassay Laboratory™ ELISA. The correlation between plasma sCD36 and the patient's characteristics (metastasis status and molecular subtype) were then analyzed. A total of 76 patients were enrolled, 36 of whom were categorized into the overweight/obese group and 40 of them in the normo-weight. Plasma levels of sCD36 in breast cancer patients were higher than controls at 0.24±0.163 ng/mL and 0.46±0.175 ng/mL, respectively (p=0.006). However, no difference in plasma sCD36 levels was found between the overweight/obese group and the normo-weight breast cancer subjects (p>0.05). Plasma sCD36 increased significantly in breast cancer patients, but no significant difference was found based on body mass index. Further research is needed to determine the role of sCD36 in determining clinical outcomes and prognosis in breast cancer patients.Keywords: Soluble CD36, body mass index, breast cancer, indonesia.